ANALISIS PENGENDALIAN MANAJEMEN YANG MEMPENGARUHI MASYARAKAT NON MUSLIM MENABUNG DI PT. BANK SYARIAH MANDIR: ANALISIS PENGENDALIAN MANAJEMEN YANG MEMPENGARUHI MASYARAKAT NON MUSLIM MENABUNG DI PT. BANK SYARIAH MANDIRI - Singgih, Tri Asmoro; Arininiswah, Isfi; Nazmi, Nurul; Sasmita, Galuh Sukma; Santoso, Suryo Budi (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2023)
This study aims to determine the factors that can affect the interest of non-Muslims to save or save at Bank Syariah Mandiri. This research method uses a qualitative approach based on case studies, and information collection is carried out by review, question and answer, and information collection. The validation method (validation) uses triangulation and source methods. This study identifies things that can influence the interest of non-Muslim customers in choosing independent Islamic banking. According to the researcher's analysis, the element of Sharia dominates because there is a fundamental prohibition that cannot be justified against usury by generating interest. The main strategy that needs to be implemented and implemented is to use the power of seizing long-term opportunities in maximizing the profits obtained (product or market). Keywords: Non-Muslim, Sharia, Factor, Strategy.